2013
DOI: 10.1007/s11033-013-2893-8
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a Δ1-pyrroline-5-carboxylate synthetase (NtP5CS) from Nitraria tangutorum Bobr. and functional comparison with its Arabidopsis homologue

Abstract: Several functional and regulatory proteins play important roles in controlling plant stress tolerance. Proline (Pro) is one of the most accumulated osmolytes correlated with tolerance to stresses. Δ(1)-Pyrroline-5-carboxylate synthetase (P5CS) is a rate-limiting enzyme in Pro biosynthesis. In the present study, we isolated the cDNA for a P5CS gene (NtP5CS) from the halophyte Nitraria tangutorum. Phylogenetic analysis and subcellular localization analysis of NtP5CS-GFP protein in onion cells showed that NtP5CS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 56 publications
2
15
0
Order By: Relevance
“…Previous studies reported that during salinity stress, synthesis of osmo-regulators was the highest in tolerant genotypes to maintain favorable plant water status inside cells (Karthikeyan et al, 2011;Li et al, 2011;Zang et al, 2011). Interestingly, when we checked the contents of most common organic osmolytes, significantly higher accumulation of trehalose, proline, and GB was found in FL478, but in Kamini, it was at par with susceptible genotypes.…”
Section: Salt-tolerant Genotype Kamini Balances Both Ion-exclusion Anmentioning
confidence: 70%
“…Previous studies reported that during salinity stress, synthesis of osmo-regulators was the highest in tolerant genotypes to maintain favorable plant water status inside cells (Karthikeyan et al, 2011;Li et al, 2011;Zang et al, 2011). Interestingly, when we checked the contents of most common organic osmolytes, significantly higher accumulation of trehalose, proline, and GB was found in FL478, but in Kamini, it was at par with susceptible genotypes.…”
Section: Salt-tolerant Genotype Kamini Balances Both Ion-exclusion Anmentioning
confidence: 70%
“…P5CS enzyme activity in sorghum ( Sorghum bicolor ) seedlings was found to be induced upon short-term heat stress (6 h at 40 °C) 52 , but inhibited under long-term heat stress, such as in wheat (5 d at 33 °C) 53 , and tomato ( Solanum lycopersicum ) (48 h at 35 °C) 54 . Similarly, transcript levels of P5CS were up-regulated by short-term heat stress in Nitraria tangutorum (6 h at 50 °C) 55 , but down-regulated by long- term heat stress in peach ( Prunus persica ) (5 d at 36.7 °C) 56 . The common up-regulation of proline synthesis by both long-term (21 d) heat and drought stress in this study suggested the importance of P5CS regulation of proline synthesis in A. stolonifera adaptation to prolonged heat and drought stress.…”
Section: Discussionmentioning
confidence: 96%
“…In the current study, the abundance in Δ 1 -pyyroline-5-carboxylate synthase (Bra005012) was decreased in resistant samples. This enzyme catalyzes the rate-limiting step of proline biosynthesis responding to environmental stresses (Zheng et al, 2014 ). Even two of the enzymes involved in arginine biosynthesis were up-regulated, the down-regulation of this key enzyme in proline biosynthesis may indicate that the P. brassicae -induced arginine catabolism and proline biosynthesis are both disrupted in resistant samples carrying Rcr1 .…”
Section: Discussionmentioning
confidence: 99%